Future Armour Materials and Technologies for Combat Platforms - Singh, B. Bhav; Sukumar, G.; Senthil, P. Ponguru; Jena, P.K.; Reddy, P.R.S.; Siva Kumar, K.; Madhu, V.; Reddy, G.M. (Defence Science Journal, 2017)
The ultimate goal of armour research is to create better armour for battle worthy combat plat forms such as main battle tanks, infantry combat vehicles and light combat vehicles. In each of these applications, the main aim boils down to one of the two things; either reduce the weight without sacrificing protection or enhance the performance at same or even reduced weight. In practice, these ambitions can be fulfilled only if we have with us, appropriate improved armour materials, advanced and innovative technologies and also improved designs, which enable us to use them for creating next generation armour modules. Armour systems have progressed through improvements in metallic, ceramic and lightweight (low areal density) composite materials. Similarly, the advances in development of explosive reactive armour (ERA) and non-explosive reactive armour (NERA) have generated efficient armour system against contemporary high explosive antitank ammunition and missile threats for the armoured vehicles. Yet, to achieve armour performance exceeding that of the current light combat vehicles and main battle tanks, further advancements in armour materials, systems, and survivability technologies are required for new vehicular systems that weigh significantly less than the present combat platforms. Various approaches and advancements in the metallic and composite armour materials, ERA and NERA systems to improve the survivability of armoured vehicles in the futuristic multi-spectral battlefield scenarios are described.